"Sometimes It's Difficult to Have a Normal Life": Results from a Qualitative Study Exploring Caregiver Burden in Schizophrenia. (3rd April 2014) - Gater, Adam; Rofail, Diana; Tolley, Chloe; Marshall, Chris; Abetz-Webb, Linda; Zarit, Steven H.; Berardo, Carmen Galani
Abstract : Objectives . As a disease typified by early onset and chronic disease course, caring for a person with schizophrenia may have a significant impact on caregivers' lives. This study aimed to investigate the subjective experiences of caregivers of people with schizophrenia as a means of understanding "caregiver burden" in this population. Methods . Face-to-face qualitative interviews were conducted with a diverse sample of 19 US-English speaking caregivers of people with schizophrenia (who were at least moderately ill). Interview transcripts were analyzed using grounded theory methods and findings used to inform the development of a preliminary conceptual model outlining caregivers' experiences. Results . Findings support assertions that people with schizophrenia were largely dependent upon caregivers for the provision of care and caregivers subsequently reported lacking time for themselves and their other responsibilities (e.g., family and work). Caregiver burden frequently manifested as detriments in physical (e.g., fatigue, sickness) and emotional well-being (e.g., depression and anxiety). Conclusions . Caring for a person with schizophrenia has a significant impact on the lives of informal (unpaid) caregivers and alleviating caregiver burden is critical for managing individual and societal costs. Future research should concentrate on establishing reliable and valid means of assessing burden among caregivers of persons with schizophrenia to inform the development and evaluation of interventions for reducing this burden.